ADVANTAGES ON MEDITATION AND ALTERED STATED OF CONSCIOUSNESS EXPERIENCES - Hendro Prabowo (Jurnal Psikologi, 2007)
Meditation comes from religion ritual basically, and then it goes to science domain, especially in psychology transpersonal. Meditation has a root from religion tradition from India, Japan, China, and Java. Nowadays, meditation is growing up faster in West and empirically using for the holistic human development. Meditation gives many advantages physically, psychologically, and socially. There are some studies support this findings, in traditional meditation and also modern meditation that using music in its processes. Some experiments are developed by meditation exercises as independent variable and some personality aspects for dependent variables. On the other hand,still, only few studies about the altered state of consciousness. Because of that this writing tries to enhancing the knowledge about the use of traditional meditation and also qualitative research related to altered state of consciousness in meditation with music. Key words: meditation, meditation with music, altered state of consciousness